Enhancing Occupational Safety through Safety Talk: Evidence from Palm Oil Processing Industry - Fatma Salsabila; Nurhayati (Karya Kesehatan Siwalima, 2026)
Workplace accidents are unexpected events occurring in occupational settings that may result in physical injury, material loss, or even death. In a palm oil mill in East Kalimantan, Indonesia, accidents are primarily associated with worker negligence, inadequate use of personal protective equipment (PPE), and unsafe working conditions. One preventive strategy implemented is the occupational health and safety (OHS) management approach through safety talk, which aims to promote safe work behavior and strengthen a safety culture. This study aims to analyze the implementation of safety talk in a palm oil mill in East Kalimantan, Indonesia. A qualitative research design with a case study approach was employed, involving key informants including the chief machinist, processing assistant, foreman, deputy foreman, and seven operators from each processing station. The findings indicate that the regular implementation of safety talk has a positive impact on improving workplace safety, enhancing OHS awareness, and reducing the incidence of occupational accidents. However, several challenges remain, including limited communication between management and workers, as well as suboptimal worker awareness. The effectiveness of the program is supported by strong managerial commitment, adequate facilities, and continuous training, as reflected in improved worker discipline and a decline in accident rates. Therefore, enhancing the quality of safety talk, strengthening OHS training, implementing reward systems, and encouraging active worker participation and accountability are strongly recommended.